Efektivitas Video Pembelajaran Anatomi terhadap Pemahaman Mahasiswa Kedokteran - Mursalin, Adhywira; Enis, Rina N.; Dewi, Hasna; Miftahurrahmah, Miftahurrahmah; Kusdiyah, Erny; Ramadhan, Ghozi F. (Universitas Sam Ratulangi, 2026)
Abstract: Understanding human anatomy, including the digestive system, is fundamental for medical students. Educational videos are increasingly recognized as an effective teaching tool to enhance student comprehension and improve their performance in practical examinations. This study aimed to evaluate the effectiveness of using educational videos on the knowledge and performance of medical students at Universitas Jambi through the practical exam scores. This was a quasi-experimental study with a pre-test and post-test design. There were 123 medical students from the 2024 cohort chosen through purposive sampling. The students were divided into two groups: experimental and control groups. The experimental group was given a video on the anatomy of the digestive system as an instructional tool, while the control group received standard teaching. Data were collected from both groups' pre-test and post-test scores. Data were analyzed using the paired and independent t-tests, which compared the scores within and between the groups to identify any significant differences. The average pre-test and post-test scores were 28.85 and 54.75 for the control group, while of the experimental group were 29.91 and 62.74, respectively. The pre-test scores showed no significant difference (p=0.071), but the post-test scores demonstrated a significant improvement in the experimental group (p=0.032). In conclusion, the educational video of anatomy of the digestive system significantly improved student knowledge and performance at Universitas Jambi. Keywords: anatomy practicum; educational video; medical students Abstrak: Pemahaman tentang anatomi, termasuk sistem pencernaan, merupakan fondasi yang esensial bagi mahasiswa kedokteran. Video edukasi semakin diakui sebagai media ajar yang efektif untuk meningkatkan pemahaman mahasiswa dan menunjang kinerja mereka dalam ujian praktikum. Penelitian ini bertujuan untuk menilai efektivitas penggunaan media ajar terhadap pemahaman dan kinerja mahasiswa melalui nilai ujian praktikum mahasiswa kedokteran di Universitas Jambi. Jenis penelitian ialah kuasi-eksperimental dengan pre-test dan post-test design. Sebanyak 123 mahasiswa kedokteran dari angkatan 2024 di Universitas Jambi dipilih melalui teknik purposive sampling. Subjek penelitian dibagi menjadi dua kelompok: kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen diberikan video tentang anatomi sistem digestif sebagai alat bantu pembelajaran, sementara kelompok kontrol menerima pembelajaran standar. Data dikumpulkan dari skor pre-test dan post-test kedua kelompok. Efektivitas video dievaluasi dengan analisis uji t berpasangan dan uji t independen untuk membandingkan skor di dalam satu kelompok dan antar kelompok. Hasil penelitian menunjukkan skor re rata pre-test dan post-test kelompok kontrol ialah 28,85 dan 54,75, sedangkan skor kelompok eksperimen ialah 29,91 dan 62,74. Secara statistik, skor pre-test tidak menunjukkan perbedaan bermakna (p=0,071), tetapi skor post-test menunjukkan peningkatan bermakna pada kelompok eksperimen (p=0,032). Simpulan penelitian ini ialah video edukasi mengenai anatomi sistem digestif secara bermakna mampu meningkatkan kinerja mahasiswa di Universitas Jambi. Kata kunci: praktikum anatomi; video ajar; mahasiswa kedokteran